A study on pattern of adverse drug reaction in an adverse drug reaction monitoring centre of a tertiary care hospital in South Kerala, India - Rajan, Ajay; T., Ramani P.; Raj, Sabitha (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Adverse drug reactions (ADR) are rated as fifth leading cause of death and accounts for approximately 5% of all hospital admissions. Under reporting of ADR from healthcare professional is considered as the contributing factor for increased morbidity and mortality. India has taken well appreciated step to launch Pharmacovigilance Programme of India (PvPI) to safeguard heath care of Indian population. This study looks into the detailed analysis of ADR reported to adverse drug reaction monitoring centre (AMC), Government Medical College, Trivandrum to assess its pattern, causality, severity and seriousness of ADR. Primary objectives of this study are the pattern of adverse drug reactions reported to ADR monitoring centre (AMC) and secondary objective is to assess causality, severity. Methods: A record based descriptive study was conducted in the ADR monitoring centre of government medical college, Trivandrum, Kerala from September 1st 2016 to February 2017(6 months). The data were collected from the all reported case records/ ADR report form of CDSCO. The details of the various adverse drug reactions were identified and analysed to find the pattern of adverse drug reactions including distribution of age, gender, causal drug group, system organ class. Also, an attempt is made to do causality assessment using WHO UMC scale and severity by using Heart wig Seigel Scale. Results: Out of 320 ADR cases, majority of reports were due to cutaneous manifestations. Most common ADRs were erythema, induration, and rash, itching. Females were 56% and males were 44%. Majority cases were of adult age group. Causality 91.88% were probably related, 75.6% were mild reaction. 25% of cases were serious. 77.5% were recovered. Antibacterial implicated 25(7.8%) followed by anti-epileptics 24 (7.5%) ADR. Conclusions: The pattern of adverse drug reactions reported to this AMC is comparable to the studies done in other parts of country. A strong need for streamlining of ADR monitoring system and reporting reemphasized by this study, which will promote the ADR reporting in healthcare professionals.